Quality of “Vousmevoyes” Ready-to-Wear Fashion Products Featuring QR Codes - Aiana Kylani; Widowati Widowati (Journal of Creativity Student, 2026)
The development of fashion products increasingly integrates cultural elements and digital technology to create innovative and functional ready-to-wear garments. This study aimed to evaluate the quality of a ready-to-wear garment with a street tech concept and QR Code integration. The Vousmevoyes product combines streetwear characteristics, batik as a cultural element, and QR Code technology integrated through embroidery on a cropped jacket. The study employed the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model combined with a descriptive quantitative approach. Product quality was evaluated by six panelists consisting of two experts and four trained experts using a five-point Likert scale. The assessment covered six aspects: design, size, aesthetics, sewing technique, garment performance, and uniqueness. The obtained scores were converted into percentages to determine the quality category. The results showed that the overall product quality achieved a score of 82.22%, categorized as very good. The highest score was obtained for the size aspect (93.33%), followed by uniqueness (86.67%) and garment performance (83.33%), while the lowest score was obtained for design (73.33%), which remained in the good category. These findings indicate that the developed garment successfully integrates cultural and digital elements while maintaining good technical and functional quality. Further development should focus on improving the visual coherence of the street tech concept, particularly in integrating the garment silhouette, batik elements, materials, and QR Code technology.